2005
DOI: 10.1093/jac/dki295
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activity of mutacin B-Ny266

Abstract: The results presented here show, for the first time, the in vivo efficacy of a mutacin (B-Ny266) against an experimental intraperitoneal infection by S. aureus in a mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 19 publications
0
44
0
1
Order By: Relevance
“…Furthermore, the identification of bacteriocin-mediated probiotic protection could aid the development of alternative bacteriocin-based therapies. It is interesting in this regard that a recent study by Mota-Meira et al (20) demonstrated that mice infected i.p. with Staphylococcus aureus and subsequently injected with mutacin, a bacteriocin produced by S. mutans, are protected from subsequent bacterial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the identification of bacteriocin-mediated probiotic protection could aid the development of alternative bacteriocin-based therapies. It is interesting in this regard that a recent study by Mota-Meira et al (20) demonstrated that mice infected i.p. with Staphylococcus aureus and subsequently injected with mutacin, a bacteriocin produced by S. mutans, are protected from subsequent bacterial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic activity of the bacteriocin producers against a number of pathogenic or antibiotic-resistant bacterial strains in the gut has been a major focus of gut microbiota studies. Several LAB bacteriocins and/or bacteriocin-producing LAB have been shown to inhibit pathogens such as Listeria monocytogenes [83,84], Clostridium difficile [8587], Staphylococcus aureus [88] and even Salmonella enteritidis [89], Some bacteriocin producers have also been reported to eliminate multidrug- or vancomycin-resistant enterococci [81,90]. Therefore, the production of bacteriocins may contribute to the beneficial activities in the gut.…”
Section: Bacteriocinsmentioning
confidence: 99%
“…However, studies with purified substances have in many cases failed to confirm toxicity (Braude & Siemienski, 1965;Tagg et al, 1976). Although intraperitoneal injection of 10 mg mutacin B-Ny266 kg 21 did not apparently affect the health of mice, these results will have to be confirmed with more relevant toxicity tests (Mota-Meira et al, 2005). The investigation of the in vitro cytotoxicities of two bacteriocins, gallidermin (Staphylococcus gallinarum) and nisin A, in comparison with those of antimicrobial peptides of eukaryotic origin, magainin I, magainin II and melittin, indicated that gallidermin was the least cytotoxic antimicrobial peptide, followed by nisin A, magainin I, magainin II and melittin.…”
Section: Bacteriocin Therapymentioning
confidence: 95%